Analisis spasial keterjangkauan retailer rokok terhadap perilaku merokok pada siswa SMA di kecamatan Wangi-Wangi dan kecamatan Wangi-Wangi Selatan kabupaten Wakatobi - Muhammad Ihsan Awaluddin; Supriyati Supriyati; Anis Fuad (Berita Kedokteran Masyarakat (BKM), 2019)
Spatial analysis the affordability of cigarette retailers on smoking behaviour high school students in Wakatobi DistrictPurpose: This study aims to analyze the spatial relationship of the affordability of cigarette retailers to the smoking behavior of high school students in the district. Wangi-Wangi and South district Wangi-Wangi, Wakatobi Regency.Method: This type of research is an analytical survey, using a cross-sectional design. With 94 samples taken randomly using a purposive sampling method.Results: Chi-square statistical tests show affordability of retailers (ρValue = 0.048), and friend smoking behavior (ρValue = 0.010) there is a statistical relationship with smoking behavior of high school students, GeoDa spatial regression test shows that affordability of retailers (p = 0.00922), friend's smoking behavior (p = 0.00204) and parents' smoking behavior (p = 0.03181) there is a spatial relationship with smoking behavior. Moran's Index is in the range of 0 <I ≤ 1 indicating positive spatial autocorrelation.Conclusion: There is a spatial relationship between the affordability of retailers, friend smoking behavior and smoking behavior of parents with smoking habits of high school students in Wangi-Wangi District and WangiWangi South District, Wakatobi Regency.